TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA DALAM E-COMMERCE YANG DIRUGIKAN AKIBAT DUGAAN ORDER FIKTIF - Bunga Andjani; Abraham Ferry Rosando (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Today, the internet is able to create a new culture among people who are certainly ready to provide various services and conveniences with commercial transactions. As a result of technological developments, the emergence of e-commerce systems is considered very practical and easy to use. However, in the procedure for buying and selling transactions in e-commerce, disputes and problems often arise. One of the problems that often harms business actors is the withholding of funds on e-commerce platforms because there are allegations of fictitious orders or counterfeit orders. On this basis, this research was conducted to analyze the legal protection for business actors through electronic transactions in Indonesia regarding the withholding of funds due to alleged fraudulent transactions. The research method used in compiling the results of this research is normative legal research. The results of this study are that the relationship between business actors and e-commerce companies is a legal partnership relationship based on a partnership agreement. Protection for business actors can be seen in Article 6 UUPK, where business actors are entitled to payment for goods and if the payment funds are withheld, then the rights of business actors can be said not to be fulfilled. In addition to the UUPK regarding legal protection for business actors whose funds are withheld due to alleged fake orders, they can also refer to Article 21 paragraph (3) of the ITE Law